Model Pengelolaan Wakaf Produktif Di Era Digital Dalam Perspektif Maqashid Syari’ah - Catur Bashori, Dhofir; Hasanah, Mifatahul; Huwaida, Hasna (Universitas Muhammadiyah Jember, 2025)
Productive waqf is an innovation in waqf management aimed at optimizing the benefits of waqf assets without diminishing their perpetuity, in line with the principle of tasbil al-thamrah. Emerging models of productive waqf include mu'aqqat (temporary waqf), cash waqf, istibdal al-waqf (exchange of waqf assets), and istitsmar amwal al-waqf (waqf fund investment). From the perspective of maqashid syariah, productive waqf contributes to the protection of five fundamental objectives of Islamic law: religion, life, intellect, lineage, and wealth. In the digital era, waqf management faces challenges such as low digital literacy among stakeholders, regulatory gaps, data security, standardized digital platforms. Nevertheless, digitalization offers significant opportunities, including expanding public participation, enhancing transparency, fostering innovation in waqf products, and improving operational efficiency. Optimizing technology-based productive waqf requires strengthening digital literacy, reforming regulations, and developing innovative waqf products based on maqashid syariah principles to sustainably support the economic development of the Muslim community